Association between hypertension and anthropometric indices in adult men: a case control study - Mankar, Sharad B.; Wakode, Santosh L.; Deshpande, Sonal; Wakode, Naina S.; Jiwtode, Manoj T.; Mishra, Neelam V. (International Journal Of Community Medicine And Public Health, 2018)
Background: Controversies over the value of BMI for the estimation of body fat have led to recommendations of the use of new methods to measure body fat. The objective of the study was to find the association between hypertension and anthropometric variables like BMI, Waist-Hip ratio, Ponderal index, Brocca index. Methods: Newly diagnosed 150 hypertensive patients aged more than 30 years attending medicine OPD were selected as cases. Equal numbers of age matched controls were selected from relative or neighbourhood. Blood pressure of the subjects was recorded. BMI, WHR, Ponderal index, Brocca index were calculated. Association between two categorical variables was analyzed by using Chi -square test, odds ratio along with 95% confidence interval (CI). Student’s T test was used as test of significance for difference between two means. P<0.05 was considered to be statistically significant. Results: Those having BMI >25 has 2.28 (1.31, 3.95) times risk of being hypertensive. Those having waist to hip ratio (WHR) >0.9 had 2.73 (1.68, 4.41) times higher chance of being hypertensive. Those having Ponderal Index <40 had 3.08 (1.75, 5.42) times higher risk of hypertension. Those with ideal body weight percent more than 100 by Brocca index had 2.98 (1.84, 4.83) times chance of getting hypertension. Conclusions: Ponderal index (PI), Ideal body weight percent by Brocca index (BI) and waist hip ratio (WHR) were found to be strongly associated with hypertension with higher odds ratio than BMI.